Experimental investigations on natural fiber reinforced composites. (2021) - Nandhakumar, S.; Mithresh Kanna, K.; Mohammed Riyas, A.; Nathin Bharath, M.
Abstract: The composite materials are used in the place of ordinary materials because of its properties like high rigidity, low warm development, high solidarity to weight proportion. The improvements of new materials are developing step by step. Blending of characteristic fiber with Polymers are finding expanded applications. Normal fiber composites, for example, Luffa and coconut fiber (coir) fiber strengthened polymer composites turned out to be progressively appealing because of their high specific quality, lightweight and biodegradability. In this investigation mechanical properties, for example, rigidity, hardness quality are assessed. For this, Natural fiber strengthened composites are fabricated utilizing pressure forming technique. These composites are thought about based on mechanical properties, for example, quality, durability, hardness and thickness and so on. The outcomes showed that the fuse of Luffa ( Luffa acutangula ), Coconut or coir ( Cocos nucefera ) fiber with polymer can improve the properties and utilized as a substitute material for Glass fiber strengthened polymer composite.